Simultaneous determination of clavulanic acid and tazobactam in bovine milk by HPLC. Issue 4 (3rd April 2017) - Guo, Peipei; Chen, Yuan; Yue, Chonghui; Yu, Guoping
ABSTRACT: A rapid and specific high-performance liquid chromatographic method was developed and validated for the simultaneous determination of the β-lactamase inhibitors clavulanic acid and tazobactam in bovine milk. The HPLC system was equipped with ultraviolet absorption detection using a C18 column with a detection wavelength of 215 nm. The mobile phase (pH 4) was 0.02% phosphoric acid and methanol in the ratio of 90:10 v/v. The retention times were 5.67 min for clavulanic acid and 7.22 min for tazobactam. The method exhibited good linearity for clavulanic acid and tazobactam, with R 2 > 0.9988. Recovery ranged from 81.953% to 87.688% for clavulanic acid and from 85.007% to 92.991% for tazobactam. The precision expressed as RSD ranged from 0.975% to 1.248% for clavulanic acid and from 0.872% to 1.650% for tazobactam. A simple and precise HPLC method was developed for the determination of clavulanic acid and tazobactam in bovine milk. This method is intended for use in surveys of milk adulteration by the relevant inspection departments. Graphical Abstract: